2020
DOI: 10.3390/su12176786
|View full text |Cite
|
Sign up to set email alerts
|

Managerial Pro-Social Rule Breaking in the Chinese Organizational Context: Conceptualization, Scale Development, and Double-Edged Sword Effect on Employees’ Sustainable Organizational Identification

Abstract: Managerial Pro-Social Rule Breaking (MPSRB) is a prevalent leadership behavior in China, characterized by conflict between favor and rule. Despite emerging interest in this behavior, two theoretical questions remain unsolved. First, its definition, dimensions, and measurement in the Chinese context are still lacking or improper; second, its double-edged sword effect on employees’ attitude is rarely empirically examined. This paper conducts three studies to solve these questions. In study 1, based on an analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This application of morality possibly permits subordinates to commit mistakes, including intentionally breaking the organizational policies. 72 Research shows that in the People's Republic of China, inclusive leadership positively supports the employee's voice behavior, encouraging the management to fulfill the needs of the new generation (ie, employees). 73 Overall, Chinese culture has significantly enhanced corporate behavior, thereby modifying historical organizational practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This application of morality possibly permits subordinates to commit mistakes, including intentionally breaking the organizational policies. 72 Research shows that in the People's Republic of China, inclusive leadership positively supports the employee's voice behavior, encouraging the management to fulfill the needs of the new generation (ie, employees). 73 Overall, Chinese culture has significantly enhanced corporate behavior, thereby modifying historical organizational practices.…”
Section: Discussionmentioning
confidence: 99%
“…This application of morality possibly permits subordinates to commit mistakes, including intentionally breaking the organizational policies. 72 …”
Section: Discussionmentioning
confidence: 99%
“…Last, but not least, managing paradoxes result from different structural and individual demands, which may lead to conflicts in the health-care organization (Lv et al , 2020), and may increase the perception of unfair or injustice results (Lv et al , 2020). Paradoxical leadership could form both stability and flexibility that assists organizations to manage and integrate multidimensional demands in a changing environment.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The leader’s effectiveness will be contingent on how appropriate the leadership style compares to the specific situation at a certain moment (Rehman et al , 2020). Nevertheless, these two opposite mechanisms under different and confront conditions, demands could conflict with each other and either separate or ignore the contradiction (Lv et al , 2020). This kind of switching leadership style could be unpredictable and complex (Zhang and Han, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When employees perceive that their leaders are inclusive, they engage in more PSRB as they believe that they are not blamed by their leaders [ 18 , 19 ]. Even though, the authors expect a positive link between inclusive leadership and PSRB as suggested by [ 8 ].…”
Section: Introductionmentioning
confidence: 99%